Direct dating of folding events by 40Ar/39Ar analysis of synkinematic muscovite from flexural-slip planes. (February 2016) - Wang, Yu; Zwingmann, Horst; Zhou, Liyun; Lo, Ching-hua; Viola, Giulio; Hao, Jinhua
Abstract: Timing of folding is usually dated indirectly, with limited isotopic dating studies reported in the literature. The present study investigated the timing of intracontinental, multi-stage folding in Upper Proterozoic sandstone, limestone, and marble near Beijing, North China, and adjacent regions. Detailed field investigations with microstructural, backscattered electron (BSE) images and electron microprobe analyses indicate that authigenic muscovite and sericite crystallized parallel to stretching lineations/striations or along thin flexural-slip surfaces, both developed during the complex deformation history of the study area, involving repeated compressional, extensional and strike-slip episodes. Muscovite/sericite separates from interlayer-slip surfaces along the limbs and from dilatant sites in the hinges of folded sandstones yield muscovite 40 Ar/ 39 Ar plateau ages of ∼158–159 Ma, whereas those from folded marble and limestone samples yield ages of 156 ± 1 Ma. Muscovite from thin flexural-slip planes on fold limbs and hinges yields ages within analytical error of ∼155–165 Ma. Further muscovite samples collected from extensionally folded limestone and strike-slip drag folds yield younger ages of 128–125 Ma with well-defined plateaus. To assess the potential influence of the detrital mica component of the host rock on the age data, two additional muscovite samples were investigated, one from a folded upper Proterozoic–Cambrian sandstone outside the Western Hills of Beijing and one from a folded sandstone sampled 20 cm from folding-related slip planes. Muscovite separates from these samples yield significantly older ages of 575 ± 2 Ma and 587 ± 2 Ma, suggesting that the timing of folding can be directly determined using the 40 Ar/ 39 Ar method. This approach enables the identification and dating of distinct deformation events that occur during multi-stage regional folding. 40 Ar/ 39 Ar dating can be used to constrain the timing of muscovite and sericite growth at moderate to low temperatures (<400 °C) during folding, yielding well-defined plateau ages and thereby the age of deformation in the upper crust. Graphical abstract: Highlights: Direct dating of fold structures using 40Ar/39Ar step-heating methods. The study area is near Beijing, China, and adjacent regions. Muscovite was dated from flexural-slip planes and fold hinges. Fluid flow, temperature and tectonic stress control determination of folding age.